2011
DOI: 10.3171/2011.1.jns10810
|View full text |Cite
|
Sign up to set email alerts
|

Double fascicular nerve transfer to the biceps and brachialis muscles after brachial plexus injury: clinical outcomes in a series of 29 cases

Abstract: Study results demonstrated the reliable restoration of M4-M5 elbow flexion following double fascicular transfer in patients with brachial plexus injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
1
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 45 publications
3
54
1
9
Order By: Relevance
“…Nerve transfers used in this study have demonstrated promising motor outcomes in the adult population and have become a first-line treatment option. [11][12][13] In contrast, the role of nerve transfers in the pediatric population has not been well described. The incidence of avulsion injuries of the upper roots is higher in adult patients in concordance with higher energy mechanisms of injury, which has an impact on decision making.…”
Section: Discussionmentioning
confidence: 86%
“…Nerve transfers used in this study have demonstrated promising motor outcomes in the adult population and have become a first-line treatment option. [11][12][13] In contrast, the role of nerve transfers in the pediatric population has not been well described. The incidence of avulsion injuries of the upper roots is higher in adult patients in concordance with higher energy mechanisms of injury, which has an impact on decision making.…”
Section: Discussionmentioning
confidence: 86%
“…Eight patients recovered grade M5, 15 patients recovered grade M4, and four patients recovered grade M3 elbow flexion strength. 52 More recently, some authors have suggested with prospective data that there is no difference in outcomes between single and double fascicular transfers for recovery of elbow flexion. 53 For restoration of ulnar intrinsic function, Novak and Mackinnon reported their results of terminal anterior interosseous nerve-to-deep motor branch of the ulnar nerve transfer in the setting of high ulnar palsy 50 with a mean follow-up time of 18 months in eight patients.…”
Section: Discussionmentioning
confidence: 98%
“…Typical indications used in our institution include brachial plexus injuries or other proximal injuries with a long distance from target motor end plates, significant limb trauma resulting in segmental loss of nerve function, and previous injury with significant scarring around vital bony or vascular structures. 2 Some of our more common transfers include those from the median nerve to the distal radial nerve or from the radial nerve to the median nerve 49 for recovery of finger and wrist extension or flexion, respectively; terminal anterior interosseous nerve-to-ulnar nerve transfer 50 to reconstruct ulnar intrinsic function; and the double fascicular transfer for recovery of elbow flexion 51,52 in brachial plexus injuries.…”
Section: Nerve Transfermentioning
confidence: 99%
“…The double fascicle transfer technique to restore elbow flexion has recently been reported to be effective in up to 97% of adult patients with brachial plexus injuries. 12 Likewise, at 22 months after surgery, our patient has demonstrated excellent recovery of elbow flexion.…”
Section: Discussionmentioning
confidence: 84%